2005
DOI: 10.1002/jmor.10368
|View full text |Cite
|
Sign up to set email alerts
|

Development of the uterine shell glands during the preovulatory and early gestation periods in oviparous and viviparous Lacerta vivipara

Abstract: The evolutionary process leading to the emergence of viviparity in Squamata consists of lengthening the period of egg retention in utero coupled with marked reduction in the thickness of the eggshell. We used light microscopy and scanning electron microscopy to study uterine structure during the reproductive cycle of oviparous and viviparous females of the reproductively bimodal Lacerta vivipara. We compared the structure of the uterine shell glands, which secrete components of the eggshell, during preovulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
1
19

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(113 citation statements)
references
References 47 publications
4
89
1
19
Order By: Relevance
“…Previous dissection of recently ovulated eggs revealed that eggshells from oviparous females were eight times heavier (dry mass, 8 mg) than the embryonic membranes of viviparous females (1 mg), whereas yolk content of ovulated ova (mean dry mass, 55 mg) did not differ between the two reproductive modes (Stewart et al, 2009). Thus oviparous and viviparous female Z. vivipara are very similar in their pre-ovulation reproductive allocation except for the synthesis of the eggshell components that are stored in the uterine glands prior to ovulation and then deposited on the fertilized ova shortly after ovulation (Heulin et al, 2005). While synthesis of these shell components requires morphological modification of uterine epithelium (Adams et al, 2004), our results suggest that preparation for egg shelling has a negligible energy demand.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Previous dissection of recently ovulated eggs revealed that eggshells from oviparous females were eight times heavier (dry mass, 8 mg) than the embryonic membranes of viviparous females (1 mg), whereas yolk content of ovulated ova (mean dry mass, 55 mg) did not differ between the two reproductive modes (Stewart et al, 2009). Thus oviparous and viviparous female Z. vivipara are very similar in their pre-ovulation reproductive allocation except for the synthesis of the eggshell components that are stored in the uterine glands prior to ovulation and then deposited on the fertilized ova shortly after ovulation (Heulin et al, 2005). While synthesis of these shell components requires morphological modification of uterine epithelium (Adams et al, 2004), our results suggest that preparation for egg shelling has a negligible energy demand.…”
Section: Discussionmentioning
confidence: 88%
“…Large windows provided natural light for about 12 h day -1 . In order to elicit reproduction and synchronize the reproductive cycles, the lizards were overwintered in the laboratory using a standard protocol (Gavaud, 1983;Heulin et al, 2005). On 1 October, lizards were placed in small boxes containing damp sand and wet moss, and these boxes were placed in a dark chamber (brand Liebherr, Dortmund, Germany) that was cooled progressively from 10 to 4°C during the first week, and then maintained at a constant 4°C thereafter.…”
Section: Animal Husbandrymentioning
confidence: 99%
See 2 more Smart Citations
“…Possibly to facilitate the flux of oxygen and carbon dioxide, squamates exhibit progressive thinning of the eggshell the longer eggs are retained before oviposition (Heulin 1990, Qualls 1999, Heulin et al 2002. The eggshell and shell membrane are thinned via reductions in either the number of shell glands present in the oviduct (Guillette 1993), or a reduction in the size of the shell gland which presumably impedes function (Heulin et al 2005). Most viviparous species retain a reduced eggshell membrane (Blackburn 1998), but it is lost during gestation in placentotrophic species (Blackburn et al 1984.…”
Section: Respiratory Gas Exchangementioning
confidence: 99%